2017
DOI: 10.4172/2476-1966.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activation Factor Receptor Induces Interleukin 10 Production through STAT3 Activation in Dendritic Cells

Abstract: The activation of the platelet-activating factor receptor (PAFR) is associated to a suppressor phenotype in macrophages and dendritic cells (DCs). In the present study, we investigated mechanisms underlying the production of the interleukin 10 (IL-10) through PAFR activation in murine DCs. For this purpose, BALB/c mice bone marrowderived DCs were differentiated by GM-CSF treatment and stimulated with LPS in the presence of the PAFR antagonist WEB2086. Signalling pathways downstream to TLR4 activation were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Zymosan recruits CREB to the IL10 promoter via PGE 2 and cyclic AMP, while LPS activates STAT3 via TLR4 receptors and IFNb. Although it has been suggested that PAF contributes to the activation of STAT3 (Koga et al, 2017), experiments did not confirm this mechanism. (F) Effect of Ptafr deletion on Y705-STAT3 phosphorylation in BMDCs stimulated with 1 mg/mL zymosan and 10 mg/mL LPS.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zymosan recruits CREB to the IL10 promoter via PGE 2 and cyclic AMP, while LPS activates STAT3 via TLR4 receptors and IFNb. Although it has been suggested that PAF contributes to the activation of STAT3 (Koga et al, 2017), experiments did not confirm this mechanism. (F) Effect of Ptafr deletion on Y705-STAT3 phosphorylation in BMDCs stimulated with 1 mg/mL zymosan and 10 mg/mL LPS.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, patients with low levels of the enzyme PAF acetylhydrolase show an increased risk for lethal anaphylaxis (Vadas et al, 2008). Recently, the list of PAF effects has been enlarged by the report of its involvement in a feedforward autocrine signaling mechanism that enhances the production of IL-10 ( Koga et al, 2013Koga et al, , 2017 and IL-23 (Rodríguez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The PAF/PAFR axis can also suppress the immune response by inducing tolerogenic dendritic cells 41 and proliferation of myeloid-derived suppressor cells 42 . In these cells, PAFR-mediated suppression involves IL10 and prostaglandin production 43 . PAFR-dependent immunosuppression was suggested to occur via activation of regulatory T cells (Tregs) 44 - 46 .…”
Section: Pafr and The Tumor Microenvironmentmentioning
confidence: 99%
“…Using an in vitro system, Lin and Lin [8] investigated the effects of different natural polysaccharides on the chemokine mediated immune therapy of human breast cancer. Move from cancer to inflammation, Koga et al [9] presented a platelet-activating factor receptor (PAFR) and signal transducer and activator of transcription 3 (STAT3) dependent signal pathway of IL-10 production by dendritic cells (DCs) during LPSstimulation. To understanding DCs better, Lin and Wang [10] briefly reviewed the roles of cytoskeletal actin and its regulators in the function of DCs, especially during the viral infections.…”
Section: Editor Notementioning
confidence: 99%